Proteinuria rebound in IgA nephropathy associated with obesity-related glomerulopathy - Matsukura, Hiro (CEN Case Rep, 2015)
IgA nephropathy (IgAN), the most prevalent primary chronic glomerulonephritis worldwide, has three major risk factors: hypertension, proteinuria >1 g/day, and severe renal lesions. Obesity also portends a poor prognosis. A Japanese boy with IgAN showed nephrotic syndrome at presentation. Pathological features resembled those of membranoproliferative glomerulonephritis (MPGN), although IgA deposition differed from MPGN and IgAN. Combination therapy improved renal lesions, but rebound deterioration of proteinuria occurred in this patient, who had marked obesity and hypertension. Serial kidney biopsy specimens were compatible with obesity-related glomerulopathy (ORG). Rebound proteinuria was apparently attributable to ORG rather than relapse and flaring up of IgAN.